Multimedia Interactive Learning on Indonesian Language Content - Ni Made Ayu Christina; Ni Nyoman Ganing (Universitas Pendidikan Ganesha, 2021)
The impact of covid-19, which requires all types of learning activities to be carried out online. As a result, teachers have limitations in finding learning media suitable for student characteristics and suitable for use in online learning conditions. The purpose of this development research was to determine the feasibility of designing interactive multimedia learning. This type of research is development research. The research model used is the ADDIE model. The subjects of this study were 3 grade III elementary school students. The data collection methods used were observation, interview and questionnaire methods. The product design test was carried out by several experts and students, learning material experts, learning design experts, instructional media experts, and individual trials consisting of three students. The form of data analysis used in this research was descriptive quantitative data analysis. Based on the results of the study, showed the feasibility percentage level of interactive multimedia according to learning material experts was 95%, the percentage level of the feasibility of interactive learning media according to learning design experts was 90%, and according to individual trials, the percentage level of the feasibility of interactive learning multimedia was 96.52% with excellent qualifications. This development research indicated that the development of interactive multimedia learning assisted was suitable for use in the learning process on Indonesian language content in literary appreciation for grade III elementary school students.